2017
DOI: 10.1186/s12957-017-1283-4
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the new TNM-staging system for thymic malignancies: impact on indication and survival

Abstract: BackgroundThe objective of this study is the evaluation of the Masaoka-Koga and the International Association for the Study of Lung Cancer (IASLC)/International Thymic Malignancy Interest Group (ITMIG) proposal for the new TNM-staging system on clinical implementation and prognosis of thymic malignancies.MethodsA retrospective study of 76 patients who underwent surgery between January 2005 and December 2015 for thymoma. Kaplan–Meier survival analysis was used to determine overall and recurrence-free survival r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
45
0
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(57 citation statements)
references
References 32 publications
5
45
0
7
Order By: Relevance
“…In our study, a significant correlation of the TNM and M-K staging system with DFS was observed ( p = 0.002 and p = 0.001), showing a substantial equivalence of both staging systems. However, in accordance with previous studies, the analyzed re-staging in the cohort according to the TNM system led to a remarkable shift towards stage I, with a downstaging of Masaoka–Koga stage II and III tumors [ 20 ]. This is due to the fact that the current TNM staging system does not differentiate between encapsulated tumors and tumors invading the thymic tissue or mediastinal fat, all classified in stage I.…”
Section: Discussionsupporting
confidence: 85%
“…In our study, a significant correlation of the TNM and M-K staging system with DFS was observed ( p = 0.002 and p = 0.001), showing a substantial equivalence of both staging systems. However, in accordance with previous studies, the analyzed re-staging in the cohort according to the TNM system led to a remarkable shift towards stage I, with a downstaging of Masaoka–Koga stage II and III tumors [ 20 ]. This is due to the fact that the current TNM staging system does not differentiate between encapsulated tumors and tumors invading the thymic tissue or mediastinal fat, all classified in stage I.…”
Section: Discussionsupporting
confidence: 85%
“…The invasive and non-invasive groups were divided according to stage, III and IV or I and II, and the high-risk and low-risk groups were divided according to type, B2, and B3 or types A, AB, and B1. When a tumor showed multiple histological components, it was classified based on the predominant component (39).…”
Section: Methodsmentioning
confidence: 99%
“…Obwohl sich die beiden Klassifikationen zu großen Teilen decken, bestehen insbesondere im Stadium III große Unterschiede [24]. So werden Tumormanifestationen an gut resezierbaren Strukturen wie dem Perikard oder der mediastinalen Pleura, die nach Masaoka-Koga als Stadium III klassifiziert werden, den niedrigeren TNM-Stadien I und II zugeordnet [25]. Weiter wurde das Stadium III für resektable Tumoren (Stadium IIIA) sowie schlechter bis häufig nicht resektable Tumoren (Stadium IIIB) differenziert (▶ Abb.…”
Section: Stagingunclassified
“…Außerdem zeigte sich, dass Patienten mit einem inkomplett resezierten Stadium-III-Befund ein schlechteres 10-Jahres-Überleben besaßen als inkomplett resezierte Stadium-IV-Tumoren (31 vs. 42 %). Dies deckt sich mit den Ergebnissen einer früheren Arbeit aus unserer Arbeitsgruppe, in der Patienten in TNM-Stadium III sogar ein schlechteres 5-Jahres-Überleben aufwiesen als Patienten des Stadiums IV (Stadium III: 54 % vs. Stadium IV: 70 %) [25]. Möglicherweise kann dieser Unterschied dadurch erklärt werden, dass für Patienten mit pleuraler Metastasierung noch lokale Behandlungsverfahren wie die Pleurektomie/Dekortikation mit anschließender hyperthermer intrathorakaler Chemotherapie (HITOC) zur Verfügung stehen, während die Infiltration zentraler, nicht resektabler Strukturen eine kurative Therapie oftmals limitiert [48].…”
Section: Prognoseunclassified